Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1001/jamaophthalmol.2018.6399
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Therapy With Prevention of Vision-Threatening Diabetic Retinopathy

Abstract: IMPORTANCE Diabetic retinopathy is the leading cause of blindness in working-age adults. Studies have suggested that statins may reduce the risk of developing diabetic retinopathy.OBJECTIVE To investigate the association between statin therapy and the development of diabetic retinopathy in patients with diabetes and dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 36 publications
3
64
1
1
Order By: Relevance
“…In the FIELD study, lipid-lowering therapy was associated with a reduced risk of lower-limb amputations, suggesting that lipid lowering may have beneficial effects on diabetic neuropathy [61]. In the aforementioned study of more than 18,000 individuals with type 2 diabetes from Taiwan, statin therapy significantly reduced the risk of new-onset diabetic neuropathy and foot ulcers [51]. While the mechanisms involved are not fully understood, oxidised LDL-cholesterol induced oxidative stress has been shown to mediate nerve damage in a mouse model of dyslipidaemia-induced neuropathy [62] and likely plays a similar role in neural injury in diabetic neuropathy [13].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FIELD study, lipid-lowering therapy was associated with a reduced risk of lower-limb amputations, suggesting that lipid lowering may have beneficial effects on diabetic neuropathy [61]. In the aforementioned study of more than 18,000 individuals with type 2 diabetes from Taiwan, statin therapy significantly reduced the risk of new-onset diabetic neuropathy and foot ulcers [51]. While the mechanisms involved are not fully understood, oxidised LDL-cholesterol induced oxidative stress has been shown to mediate nerve damage in a mouse model of dyslipidaemia-induced neuropathy [62] and likely plays a similar role in neural injury in diabetic neuropathy [13].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationsmentioning
confidence: 99%
“…Several small uncontrolled studies examining the effects of statin use on diabetic retinopathy risk found a beneficial effect [47,48] but were contradicted by larger studies [49,50]. On the other hand, a recent well-conducted large study in Taiwan, of more than 18,000 individuals with type 2 diabetes with age and sexmatched controls, found that statin use significantly reduced retinopathy risk, diminished the incidence of macular oedema and reduced the need for further interventions [51]. Moreover, the FIELD and ACCORD Eye studies found that fenofibrate use significantly lowered the risk of diabetic retinopathy progression and/or the need for laser intervention in diabetic individuals [52,53].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationsmentioning
confidence: 99%
“…There are no obvious early symptoms in diabetic retinopathy [2]; hence, when visual problems begin, retinopathy has already advanced to almost a point of no return [4]. Laser therapy is the mainly effective therapy for preservation of sight in proliferative retinopathy [5]; however, it is not effective for reversing visual loss [5]. DR is a progressive disease characterized by visible microvascular alterations, including retinal ischemia-reperfusion injury, inflammation, abnormal permeability, neovascularization and macular edema [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is induced by diabetes, which causes the pathology of retinal capillaries, arterioles and venules, and the subsequent effects of leakage from or occlusion of small vessels [2224]. Laser therapy is the mainly effective therapy for preservation of sight in proliferative retinopathy [24]; however, it is poor to reverse visual loss. Hence, it is still to find the new therapies to improve the effective of DR.…”
Section: Discussionmentioning
confidence: 99%